2023
DOI: 10.26434/chemrxiv-2023-jp5nt
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Towards multi-scale measurement-informed methane inventories: reconciling bottom-up inventories with top-down measurements using continuous monitoring systems

Abstract: Government policies and corporate strategies aimed at reducing methane emissions from the oil and gas sector increasingly rely on measurement-informed emissions inventories, as conventional bottom-up inventories poorly capture temporal variability and the heavy-tailed nature of methane emissions. This work is based on an 11-month methane measurement campaign at oil and gas production sites. We find that basin- and operator-level top-down measurements show lower methane emissions during end-of-project than duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 23 publications
(39 reference statements)
1
5
0
Order By: Relevance
“…A full sensitivity study of the framework parameters is provided in the supporting information (SI) file. The proposed framework has also been used on multiple oil and gas production sites, with results closely in line with other top-down measurement techniques (Daniels et al, 2023).…”
Section: Introductionsupporting
confidence: 58%
“…A full sensitivity study of the framework parameters is provided in the supporting information (SI) file. The proposed framework has also been used on multiple oil and gas production sites, with results closely in line with other top-down measurement techniques (Daniels et al, 2023).…”
Section: Introductionsupporting
confidence: 58%
“…Most field studies of methane emissions from oil and gas facilities using new technologies, such as aircrafts and satellites, provide snapshot measurement data; while they are detailed in spatial extent, they do not track the variation of individual component-level emissions. , This is critical because measurements have revealed significant differences in emissions across seasons, time of day, and other temporal variables. Furthermore, recent studies have found that emission intermittency impacts the effectiveness of LDAR surveys as well as emission estimates. , Currently, only one study has empirically demonstrated emission reductions from regulatory LDAR programs with data from a small number of facilities …”
Section: Introductionmentioning
confidence: 99%
“…These new technologies have been extensively tested under controlled release conditions to evaluate performance parameters such as probability of detection curves and quantification accuracy (1)(2)(3)(4). As a result, several operators are now deploying these technologies for cost-effective leak detection and mitigation (5)(6)(7)(8)(9). Recent field campaigns have also demonstrated that top-down measurement approaches identify emissions events that are typically missed by ground-based surveys (10).…”
Section: Introductionmentioning
confidence: 99%
“…A key factor that makes LDAR surveys using site-wide screening technologies cost-effective is the presence of large methane emitters that are often missed by OGI-based LDAR programs. Recent studies have demonstrated the role of intermittent emission events in contributing to a large fraction of total emissions across the oil and gas supply chain (5,6,(16)(17)(18). In using the FEAST model, EPA explicitly incorporated large emitters to determine equivalency of OGI-based LDAR program with those that use new technologies.…”
Section: Introductionmentioning
confidence: 99%